Diagram Kontrol Short-Run untuk Memantau Variabilitas Proses - Budi Nugroho; Desi Yuniarti; Sri Wahyuningsih (Program Studi Statistika FMIPA Universitas Mulawarman, 2019)
Short run control chart is designed for production small scale and a limited amount data for monitoring different characteristic on same diagram control. The purpose of research is to know the implementation of short run control chart for monitoring mean and variability process based on characteristic data 1 inch Polyvinyl Chloride (PVC) in PT. Maspion. The objective of characteristics 1 inch pipe in this research are socket external diameter, socket internal diameter, barrel external diameter and barrel internal diameter. The Results showed that controlling process of by applying influence function, effective is to be applied to detect small movement in observation 11, 14, 14 and 9 for every control chart characteristic limited control 3σ.